ANALISIS AKUNTANSI PERTANGGUNGJAWABAN DALAM MENILAI KINERJA PUSKESMAS SEMPAJA TAHUN ANGGARAN 2018 - Wahyuni Kumala Sari; Erni Setiawati (University of Widya Gama Mahakam Samarinda, 2021)
This study aims to determine whether the accounting for accountability For the use of the expenditure budget that has been given by the government to the community health center has been carried out economically and effectively and to analyze the achievement of the performance of budget management and accountability for the use expenditure budget in samarinda city sempaja community health center in carrying out and funding organizational activities. The analytical method used in this research is quantitative research using measurement effectiveness analysis and economic analysis. The data used in this study are reports on budget work plans and plans for implementing activities as well as reports on implementing budget activities. Data collection techniques used in this research are field research including interview and document studies and literature review. The results of the analysis of this study are based on calculation data of effectiveness analyzing and economic analysis by analyzing the budget, realization and the target of its activities shows that accountability accounting in achieving the performance of sempaja community health center in 2018 has been carried out quite effectively and economically in accounting for the implementation of targeted activities and funding for puskesmas activities sempaja